Magnetic and transport studies of [sigma]-phase Fe50V50 alloys with different thermal history - Costa, B. F. O. (2008)
http://www.sciencedirect.com/science/article/B6TXM-4TRM3MB-3/2/a3801608d0695335d1eccf6692a4287d